La peur dans le roman policier français du XIXe siècle : l’angoisse face à la modernité - Fernandez, Virginie (Romanica Silesiana)
In the nineteenth century, Paris was an uncertain place due to several causes. The middle-class felt a threat to a society which was being redefined in an unexpected way and lost its traditional marks. Paris, as a mythical and symbolic city, offers then an ideal framework to the detective novel from its origins, kind of novels that spreads the insinuation of the danger in the city. Emile Gaboriau, father of the French detective novel, plays on the fear and the anxiety towards this changing world. The capital presents a dark and scary atmosphere convenient to the mystery and crime. Thus, the lower class is seen as wild and dangerous; the city which spreads out presents blurred and disturbing borders; finally, the night strengthens the dark face of Paris exciting the fantasies and emphasizing the fears. Key words: detective novel, Paris, nineteenth century, night, crime, border, popular class